Euthanasia Active in Perspective of Islamic Inheritance: An Overview of Islamic Law - Yakin, Ainul; Syafi’ie, Musta’in (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
Science and technology experience rapid development and progress. This is due to the increasing number of modern discoveries. Among the technological discoveries that are very important are inventions in the field of medicine. With modern medical equipment, a patient's suffering can be alleviated. But in reality, there are still some patients who cannot be avoided from severe suffering. Patients suffering prologed pain bring out compassion from the family. To release his suffering, the family who cannot bear to see his condition asks the doctor to take actions that can shorten the life of the patient, this kind of action in medicine is known as euthanasia. The Purpose of this research to find out how the position of inheritance rights for applicants of active euthanasia in the view of Islamic inheritance. This research uses library research by collecting books and scientific works related to the problem being discussed. The results of this study indicate that active euthanasia carried out by the hospital at the request of the heirs is seen as a barrier to inheritance, because it includes intentional and planned killings. Heirs are also seen as too hasty to get the right of inheritance.